A method for synthesizing a light stabilizer, tinuvin-1600, using a solvent-free condensation technique

CN122916933APending Publication Date: 2026-10-16WEI HAI JIN WEI HUA XUE GONG YE YOU XIAN ZE REN GONG SI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611204543.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]本申请实施的目的在于提供一种无溶剂缩合技术合成光稳定剂TINUVIN-1600的方法,以解决现有合成路线普遍依赖邻二氯苯、DMF等高沸点有毒溶剂,导致VOCs、有机废水排放高,产物品质差,分离工艺繁杂、处理成本高的技术问题

Benefits of technology

1、本申请摒弃了使用惰性溶剂,反应物(联苯、中间体等)在熔融态下直接作为分散介质;结合高转速搅拌,体系虽然粘度高于溶剂体系,但单位体积内的反应物有效碰撞频率显著提升,消除了溶剂层对活性位点的屏蔽效应;在傅克反应与缩合反应中,无溶剂状态使得中间体在熔融体系中的浓度梯度增大,有利于反应向正方向进行;相比溶剂法因稀释导致的反应速率下降,本申请通过分段式升温精准匹配各阶段活化能需求,在无溶剂条件下实现了动力学与热力学的统一;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916933A_ABST
    Figure CN122916933A_ABST
Patent Text Reader

Abstract

The application discloses a method for synthesizing a light stabilizer TINUVIN-1600 by a solvent-free condensation technology, and belongs to the technical field of ultraviolet absorber preparation. The method is characterized in that: biphenyl, cyanuric chloride, resorcinol and halogenated isooctane are used as raw materials, and the synthesis of TINUVIN-1600 is realized through three steps of continuous solvent-free reaction, namely, a Friedel-Crafts reaction, solvent-free condensation and solvent-free etherification. In the process, a molten-state reaction system is used throughout, and a high-efficiency solid catalyst and a strengthened mass transfer design are used without any solvent. The catalyst can be recycled and used, the product has high purity and high yield, the energy consumption is significantly reduced compared with a traditional process, waste water is only washing water, VOCs emission is avoided, the method meets the requirements of green chemical industry, and is suitable for industrialized large-scale production of TINUVIN-1600 for high-end polymer materials such as polycarbonates and photovoltaic films.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of ultraviolet absorber preparation technology, and in particular relates to a method for synthesizing the light stabilizer TINUVIN-1600 using a solvent-free condensation technique. Background Technology

[0002] TINUVIN-1600 (2,4-diphenyl-6-(2-hydroxy-4-isooctyloxy)phenyl-1,3,5-triazine, UV-1600) is a high-performance hydroxyphenyl triazine ultraviolet absorber. This class of compounds exhibits extremely low volatility, excellent ultraviolet absorption efficiency, and good compatibility with various polymer substrates, without affecting the transparency and coloring properties of the finished product. Compared to traditional benzotriazole and benzophenone ultraviolet absorbers, TINUVIN-1600 provides superior weather resistance and longer-lasting protection for high-performance thermoplastics such as polycarbonate, polyester, and polymethyl methacrylate, with a lower required dosage. Therefore, TINUVIN-1600 is widely used in high-end polymer materials fields such as photovoltaic films, window films, display protective films, and polycarbonate sheets for building applications.

[0003] Currently, there are limited reports on the preparation methods of TINUVIN-1600. In existing technologies, the synthesis of TINUVIN-1600 is mainly achieved through the following route: using biphenyl, cyanuric chloride, resorcinol and haloisooctane as raw materials, the target molecule is constructed in three steps: Friedel-Crafts reaction, condensation reaction and etherification reaction. However, the existing synthesis process generally has the following problems: (i) a large amount of toxic organic solvents are used, resulting in serious VOC emissions; in the traditional process, each step of the reaction must be carried out in an organic solvent medium. For example, haloaromatic hydrocarbons such as o-dichlorobenzene, chlorobenzene or nitrobenzene are often used as solvents in the Friedel-Crafts reaction stage; high-boiling-point polar solvents such as N,N-dimethylformamide (DMF) are widely used in the condensation and etherification stages; these solvents not only have high toxicity, but also volatilize in large quantities during the reaction, causing serious VOCs (volatile organic compounds) emission problems, posing a threat to the health of operators and environmental safety; (ii) Product separation and purification are difficult and the process is complex; due to the use of high-boiling-point water-soluble solvents such as DMF, the product and unreacted potassium carbonate and byproduct KBr precipitate out at the same time, making separation very difficult; existing technologies usually adopt a two-step method of first distilling off the water-soluble solvent and then adding a non-water-soluble solvent (such as heptane) for separation. This process is not only complex to operate, but also requires the use of two solvents at the same time, increasing the equipment investment and operating costs for solvent recovery; (iii) It is difficult to balance product yield and purity. The total yield of traditional solvent-based processes is usually only 38-41%, and the purity of the product can only reach 97-98%, often requiring multiple refining processes to meet the requirements of high-end polymer materials. Solvent residue also affects the application of the product in optical-grade materials. (iv) High energy consumption and high environmental treatment costs. The use of large amounts of organic solvents not only increases energy consumption in the reaction process, but also generates organic wastewater with high COD (chemical oxygen demand), resulting in high treatment costs. In addition, the distillation and recovery of solvents requires specialized recovery equipment, further increasing fixed asset investment and operating costs. In summary, the existing synthesis technology of TINUVIN-1600 is difficult to meet the requirements of large-scale production of light stabilizers in the fields of green chemistry and high-end polymer materials. Developing a green, environmentally friendly, easy-to-operate, high-yield, high-purity, and industrially suitable synthesis method for TINUVIN-1600 has important practical significance and application value. Summary of the Invention

[0004] The purpose of this application is to provide a method for synthesizing the light stabilizer TINUVIN-1600 using solvent-free condensation technology, in order to solve the technical problems of existing synthesis routes generally relying on high-boiling-point toxic solvents such as o-dichlorobenzene and DMF, resulting in high VOCs and organic wastewater emissions, poor product quality, complicated separation processes, and high treatment costs.

[0005] To achieve the above objectives, the technical solution adopted in this application is: to provide a method for synthesizing the light stabilizer TINUVIN-1600 using solvent-free condensation technology, specifically including the following steps: (a) Friedel-Crafts reaction: Biphenyl and cyanuric chloride are added to a reaction vessel in a gas atmosphere and melted, and then a solid acid catalyst is added to carry out a Friedel-Crafts reaction to generate intermediate A; (ii) Solvent-free condensation: The intermediate A is mixed and melted with resorcinol, trifluoromethanesulfonic acid co-catalyst is added, and the condensation reaction is carried out by staged heating, and the intermediate B is generated by post-processing. (III) Solvent-free etherification: The intermediate B and the basic compound catalyst are added to the reaction vessel, and haloisooctane is added in a gas atmosphere to carry out the etherification reaction. After post-treatment, TINUVIN-1600 is obtained. In one embodiment, The molar ratio of biphenyl to cyanuric chloride is 1:0.4-0.6; the molar ratio of intermediate A to resorcinol is 1:1.0-1.5; and the molar ratio of intermediate B to isooctane is 1:2.2-2.5.

[0006] In one embodiment, The solid acid catalyst in step (i) is one of montmorillonite-supported aluminum trichloride, Amberlyst 15 cation exchange resin, or sulfonated graphene; the molar ratio of biphenyl to solid acid catalyst is 1:0.3-0.6.

[0007] In one embodiment, In step (1), the gas atmosphere is nitrogen, the melting temperature is 80-85 ℃, the Friedel-Crafts reaction temperature is 95-100 ℃, and the time is 6-8 h.

[0008] In one embodiment, The melting temperature in step (ii) is 110 °C, the dropping temperature of the trifluoromethanesulfonic acid co-catalyst is 115-120 °C, the dropping time is 30 min, and the molar ratio of intermediate A to the trifluoromethanesulfonic acid co-catalyst is 1:0.05-0.08.

[0009] In one embodiment, The segmented heating in step (II) is as follows: react at 120 ℃ for 3 h, and react at 125-130 ℃ for 4-5 h.

[0010] In one embodiment, The post-treatment described in step (II) is as follows: add one times the amount of deionized water to the system for crystallization, and wash the crystallized solid with hot water at 70 ℃.

[0011] In one embodiment, The alkaline composite catalyst in step (iii) is a mixture of potassium carbonate and a quaternary ammonium salt, wherein the quaternary ammonium salt is one of tetrabutylammonium bromide, trioctylmethylammonium chloride, or Aliquat 336; the molar ratio of the quaternary ammonium salt to potassium carbonate is 1:18-22; and the molar ratio of intermediate B to the alkaline composite catalyst is 1:2.3-2.5.

[0012] In one embodiment, Step (3) The temperature at which haloisooctane is added is 90 °C, the temperature of the etherification reaction is 90-100 °C, and the time is 10-12 h; the haloisooctane is bromoisooctane or chloroisooctane.

[0013] In one embodiment, The post-treatment described in step (iii) is as follows: After the reaction is completed, the temperature is lowered to 50 °C, 1.5 times the volume of saturated brine is added and stirred for 30 min. After standing and separating into layers, the upper organic phase is taken out, excess bromoisooctane is removed by vacuum distillation, and then recrystallized with n-heptane. After filtration and drying, the TINUVIN-1600 product is obtained.

[0014] This application provides a solvent-free condensation technique for synthesizing the light stabilizer TINUVIN-1600, which has the following advantages compared with the prior art: 1. This application abandons the use of inert solvents, and the reactants (biphenyl, intermediates, etc.) are directly used as dispersion media in the molten state. Combined with high-speed stirring, although the viscosity of the system is higher than that of the solvent system, the effective collision frequency of the reactants per unit volume is significantly increased, eliminating the shielding effect of the solvent layer on the active sites. In Friedel-Crafts and condensation reactions, the solvent-free state increases the concentration gradient of intermediates in the molten system, which is conducive to the reaction proceeding in the forward direction. Compared with the reaction rate decrease caused by dilution in the solvent method, this application achieves the unity of kinetics and thermodynamics under solvent-free conditions by precisely matching the activation energy requirements of each stage through segmented heating. 2. The acid catalysis uses a solid superacid, whose surface Lewis acid center can more efficiently polarize the C-Cl bond of cyanuric chloride in a solvent-free, high-concentration system, promoting electrophilic substitution. After the reaction, it can be recovered by simple filtration, and the activity retention rate is high after recovery, avoiding the large amount of acidic wastewater and corrosive problems generated by the hydrolysis of traditional homogeneous AlCl3. The etherification reaction uses quaternary ammonium salt as a phase transfer catalyst. The quaternary ammonium salt cation "extracts" the carbonate ion in potassium carbonate into the organic molten phase, transforming the originally heterogeneous solid-liquid reaction into a homogeneous reaction, which greatly reduces the activation energy of the etherification reaction. Therefore, the conversion can be completed efficiently at low temperature conditions without DMF. 3. This application utilizes a molten reaction system throughout the entire process, coupled with a highly efficient solid catalyst and enhanced mass transfer design. No solvent is introduced, thus eliminating the pathway for solvent-induced side reactions at the source. Post-treatment involves only cooling crystallization and recrystallization with n-heptane. Since the system contains no high-boiling-point residues, intermediate B can be directly precipitated as high-purity crystals through hydrolysis (destroying excess trifluoromethanesulfonic acid complex), eliminating the need for multiple purification processes. The recrystallization process of the final product is merely physical impurity removal, utilizing the difference in solubility of different components in heptane to achieve high purity through a single crystallization. Because no organic solvent participates in the reaction, the wastewater is only washing water, containing only unreacted resorcinol and a small amount of inorganic salts, with a COD ≤ 1000. The concentration of TINUVIN-1600 is mg / L, and its treatment cost is far lower than that of emulsion-type high-concentration wastewater containing DMF / o-dichlorobenzene. In addition, the energy consumption of traditional processes is mainly consumed in the distillation and recovery of large amounts of solvent, while this application only consumes energy in the post-treatment recovery of heptane. Moreover, the reaction itself is used to maintain the molten state throughout the entire process, resulting in extremely high heat utilization and significantly reduced energy consumption. The catalyst retains good activity after multiple recovery processes, which greatly reduces production costs. The entire process achieves the green chemistry goal of reducing pollution and increasing efficiency, and is suitable for the large-scale industrial production of TINUVIN-1600 for high-end polymer materials such as polycarbonate and photovoltaic films. Attached Figure Description

[0015] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0016] Figure 1 The reaction equation for Example 1 is shown below. Figure 2 This is a purity diagram of intermediate A from Example 1; Figure 3 This is a purity diagram of intermediate B from Example 1; Figure 4 The purity diagram of TINUVIN1600 in Example 1; Figure 5 The infrared spectrum of TINUVIN1600 in Example 1; Figure 6 The TINUVIN1600 proton NMR spectrum of Example 1; Figure 7 The TINUVIN1600 carbon spectrum is shown in Example 1. Detailed Implementation

[0017] To make the technical problems, technical solutions, and beneficial effects to be solved by this application clearer, this application will be further described in detail. It should be understood that the specific embodiments described herein are only for explaining this application and are not intended to limit this application.

[0018] Example 1 A method for synthesizing the light stabilizer TINUVIN-1600 using solvent-free condensation technology, the reaction equation is as follows: Figure 1 As shown, the specific steps include: (I) Friedel-Crafts Reaction: A 500 ml four-necked reaction flask was equipped with a mechanical stirrer, thermometer, nitrogen delivery tube, and reflux condenser. Nitrogen was continuously used to purge the air from the reactor three times, with a constant nitrogen pressure protection (nitrogen flow rate 13 mL / min). 15.4 g (0.1 mol) of biphenyl and 9.2 g (0.05 mol) of cyanuric chloride were added sequentially. The mixture was stirred and heated to 80-85 °C at a stirring speed of 400-500 r / min, and kept at this temperature until both solids were completely melted, resulting in a homogeneous and transparent liquid (biphenyl melting point 69-71 °C; at 80-85 °C, biphenyl completely melts into a liquid aromatic medium; cyanuric chloride is soluble in hot-melted biphenyl, ultimately forming a homogeneous solution). Activated (vacuum dried at 120 °C for 2 h) montmorillonite-supported aluminum trichloride (0.05 mol, molar ratio of montmorillonite to aluminum trichloride 1:1) was added all at once. After stirring until homogeneous, the temperature was raised to 98 °C. The reaction was carried out at ℃ with constant stirring for 7 h. After the reaction was completed, the temperature was lowered, and the molten reactant was filtered to separate the montmorillonite-supported aluminum trichloride catalyst for recycling. The organic phase was washed with water until neutral, and a small amount of low-boiling impurities were removed by vacuum distillation. After cooling and crystallization, recrystallization with ethanol and vacuum drying, a white solid intermediate A (2,4-diphenyl-6-chloro-1,3,5-triazine) was obtained with a molar yield of 85%. Figure 2 As shown, the purity reaches over 99%; (II) Solvent-free condensation: A dry 500 ml four-necked reaction flask was used. Under nitrogen protection, 39.5 g (0.1 mol) of intermediate A and 14.3 g (0.13 mol) of resorcinol were added. The mixture was stirred and heated to 110 °C at a stirring speed of 500-600 r / min until the materials were completely melted and mixed. 1.2 g (0.008 mol) of trifluoromethanesulfonic acid co-catalyst was slowly added dropwise over 30 min at a constant pressure dropping funnel at 118 °C. After the addition was complete, segmented temperature control was implemented: reaction at 120 °C for 3 h, and reaction at 128 °C for 4.5 h. After the reaction was complete, heating was stopped, and deionized water was added for crystallization. The volume of deionized water was twice the volume of the melt. 70 The crystalline solid was washed with hot water at ℃ to remove unreacted resorcinol and acidic auxiliaries, yielding a pale yellow solid intermediate B (2,4-diphenyl-6-(2,4-dihydroxy)phenyl-1,3,5-triazine) in molar yield of 81%. Figure 3 As shown, the purity reaches over 99%; (III) Solvent-free etherification: Dry a 500 ml four-necked reaction flask, purge with nitrogen three times, add 48.3 g (0.1 mol) of intermediate B and 33.2 g (0.24 mol) of alkaline compound catalyst (prepared according to the molar ratio of tetrabutylammonium bromide and potassium carbonate of 1:20), stir and heat to 90 ℃ to melt, stirring speed 600-700 r / min. 44.4 g (0.23 mol) of bromoisooctane was added dropwise at a constant pressure dropping funnel at a constant rate, with the temperature maintained at 90 °C throughout the addition, for a total duration of 2.5 h. After the addition was complete, the temperature was raised to 100 °C, and the reaction was carried out under nitrogen atmosphere with stirring for 11 h. After the reaction was completed, the system was cooled to 50 °C, and 1.5 times its volume of saturated brine was added. The mixture was then stirred and washed with water for 30 min. After standing and separating into layers, the upper organic phase was removed. Excess unreacted bromoisooctane was removed by vacuum distillation, and the product was recrystallized from n-heptane. After filtration and drying, a pale yellow TINUVIN-1600 product was obtained, with a molar yield of 82%. Figure 4 As shown, the purity is above 99%, the melting point is 118-121 ℃, and the structural characterization is as follows. Figure 5-7 As shown, the total yield of the three steps is 85*81*82*100%=56.45%.

[0019] Example 2 The difference between this embodiment and Example 1 is that the amount of cyanuric chloride added is 7.4 g, the molar ratio of biphenyl to cyanuric chloride is 1:0.4, the rest of the operation is the same, the reaction yield is 66.4%, and the product purity is 91.3%.

[0020] Example 3 The difference between this embodiment and Example 1 is that the amount of cyanuric chloride added is 11.1 g, the molar ratio of biphenyl to cyanuric chloride is 1:0.6, the rest of the operation is the same, the reaction yield is 83.8%, and the product purity is 93.5%.

[0021] Example 4 The difference between this embodiment and Example 1 is that the amount of cyanuric chloride added is 5.5 g, the molar ratio of biphenyl to cyanuric chloride is 1:0.3, the rest of the operation is the same, the reaction yield is 60%, and the product purity is 88%.

[0022] As can be seen from Examples 1-4, further increasing the proportion of cyanuric chloride did not significantly improve the yield, but instead led to an increase in the amount of by-products and a decrease in product purity. The experimental results show that when the molar ratio of biphenyl to cyanuric chloride is 1:0.5, the reaction yield reaches the highest value of 85%, and the product purity also reaches the highest value of 99%.

[0023] Example 5 The difference between this embodiment and Example 1 is that the molar ratio of biphenyl and solid acid catalyst montmorillonite-supported aluminum trichloride is 1:0.3. The rest of the operation is the same, the reaction yield is 56%, and the product purity is 69%.

[0024] Example 6 The difference between this embodiment and Example 1 is that the molar ratio of biphenyl and solid acid catalyst montmorillonite-supported aluminum trichloride is 1:0.6. The rest of the operation is the same, the reaction yield is 72%, and the product purity is 85%.

[0025] Examples 1, 5, and 6 show that when the molar ratio of biphenyl to catalyst is 1:0.3, the raw material cannot be fully activated, a large amount of substrate remains in the form of raw material, and there are many reaction byproducts. When the molar ratio of biphenyl to catalyst is 1:0.6, the raw material will be decomposed and destroyed, and side reactions will also occur.

[0026] Example 7 The difference between this embodiment and Example 1 is that the Friedel-Crafts reaction temperature is 90 °C, while the rest of the operation is the same, and the reaction yield is 75%.

[0027] Example 8 The difference between this embodiment and Example 1 is that the Friedel-Crafts reaction temperature is 105 °C, while the rest of the operation is the same, and the reaction yield is 78%.

[0028] To investigate the effect of temperature on the synthesis of intermediate A, a series of experiments were conducted at different temperatures. As shown in Examples 1, 7, and 8, at lower temperatures (90 °C), the reaction rate was slower, the time required for the reaction to complete was significantly longer, and the yield was lower. However, when the temperature was further increased to 105 °C, the yield was 78%, showing a downward trend. This may be due to side reactions triggered by high temperature or the decomposition of some raw materials. In addition, high-performance liquid chromatography analysis revealed that the impurity content in the product increased significantly under high temperature conditions. Considering the reaction rate, yield, and product purity, 98 °C was determined to be the optimal reaction temperature.

[0029] Example 9 The difference between this embodiment and Example 1 is that the Friedel-Crafts reaction time is 5 hours, while the rest of the operation is the same, and the reaction yield is 78%.

[0030] Example 10 The difference between this embodiment and Example 1 is that the Friedel-Crafts reaction time is 9 hours, while the other operations are the same. The reaction yield is 85% and the product purity is 90%.

[0031] To find the optimal reaction time, reaction experiments were conducted at different times. As shown in Examples 1, 9, and 10, when the reaction time was 5 hours, the system was not completely converted, and the yield was only 78%. When the reaction time was extended to 7 hours, the yield increased significantly, and the purity of the product reached over 99%. However, when the reaction time was further extended to 9 hours, the yield did not increase significantly. Instead, the impurity content increased slightly due to the occurrence of side reactions, resulting in a decrease in purity to only 90%. Based on the experimental results, 7 hours was determined to be the optimal reaction time.

[0032] Example 11 The difference between this embodiment and Example 1 is that the amount of resorcinol added is 11 g, the molar ratio of intermediate A to resorcinol is 1:1.0, the rest of the operation is the same, and the reaction yield is 75.6%.

[0033] Example 12 The difference between this example and Example 1 is that the amount of resorcinol added is 16.5 g, the molar ratio of intermediate A to resorcinol is 1:1.5, the rest of the operation is the same, and the reaction yield is 78%.

[0034] Examples 1, 11, and 12 show that when the molar ratio increases from 1:1.0 to 1:1.3, the yield of intermediate B of the target product increases from 75.6% to 81%. This is mainly attributed to the fact that excess resorcinol can effectively promote the forward reaction and reduce the residue of unreacted intermediate A. However, when the molar ratio is further increased to 1:1.5, the yield decreases to 78%, possibly because the excessively high concentration of resorcinol leads to an increase in side reactions, thereby reducing the selectivity of the target product.

[0035] Example 13 The difference between this embodiment and Example 1 is that the amount of trifluoromethanesulfonic acid added is 0.9 g, the molar ratio of intermediate A to trifluoromethanesulfonic acid is 1:0.06, the rest of the operation is the same, and the reaction yield is 68%.

[0036] Example 14 The difference between this embodiment and Example 1 is that the amount of trifluoromethanesulfonic acid added is 1.5 g, the molar ratio of intermediate A to trifluoromethanesulfonic acid is 1:0.1, the rest of the operation is the same, the reaction yield is 81.6%, and the product purity is 94.5%.

[0037] Trifluoromethanesulfonic acid plays a crucial role as a catalyst in the synthesis of intermediate B. Examples 1, 13, and 14 show a clear optimization range for catalyst dosage. When the molar amount of trifluoromethanesulfonic acid is 0.06 times that of intermediate A, the reaction rate is significantly lower, the reaction time is extended to 12 hours, and the yield is only 68%. This is mainly because insufficient catalyst concentration fails to fully activate the reactant molecules, leading to incomplete reaction. When the catalyst dosage exceeds 0.10 times that of intermediate A, although the reaction rate increases, the product purity decreases to 94.5%. This may be because excessive catalyst triggers over-acylation or other side reactions, generating more impurities. Considering both reaction rate and product purity, the molar ratio of intermediate A to trifluoromethanesulfonic acid co-catalyst was determined to be 1:0.08. At this ratio, the reaction rate is moderate, and the product yield and purity reach 81% and 99%, respectively.

[0038] Example 15 The difference between this embodiment and Example 1 is that the solventless condensation temperature is 110 °C, and segmented temperature control is not used. The rest of the operation is the same, and the reaction yield is 76%.

[0039] Example 16 The difference between this embodiment and Example 1 is that the solventless condensation temperature is 140 °C, and segmented temperature control is not used. The rest of the operation is the same, the reaction yield is 79%, and the product purity is 93.9%.

[0040] Reaction temperature is one of the important factors affecting the synthesis efficiency of intermediate B. As can be seen from Examples 1, 15, and 16, without segmented temperature control, the reaction rate is slow in the low-temperature region (110 °C), resulting in incomplete reaction and a yield of only 76% for intermediate B. While the reaction rate is faster in the high-temperature region (140 °C), the product purity drops significantly to 93.9% due to increased side reactions. Therefore, a segmented temperature control strategy is adopted to balance reaction rate and selectivity. Specifically, the first stage is carried out at 120 °C for 3 h, which allows most of the raw materials to be converted into the target product. The second stage is heated to 128 °C and continued for 4.5 h, which helps to further promote the complete reaction and improve product purity. Experimental data show that under these optimized conditions, the yield of intermediate B can reach 81% and the purity can reach 99%.

[0041] Example 17 The difference between this embodiment and Example 1 is that the amount of bromoisooctane added is 42.5 g, the molar ratio of intermediate B to haloisooctane is 1:2.2, the rest of the operation is the same, the product yield is 76% and the purity is 97%.

[0042] Example 18 The difference between this embodiment and Example 1 is that the amount of bromoisooctane added is 48.3 g, the molar ratio of intermediate B to haloisooctane is 1:2.5, the rest of the operation is the same, and the product yield is 81.5%.

[0043] As can be seen from Examples 1, 17, and 18, when the molar ratio is 1:2.2, both the yield and purity of the target product decrease. When the molar ratio is 1:2.5, the yield of the target product does not increase significantly, but the complexity of post-processing is increased.

[0044] Example 19 The difference between this embodiment and Example 1 is that the amount of alkaline composite catalyst added is 27.7 g, the molar ratio of intermediate B to alkaline composite catalyst is 1:2.0, the rest of the operation is the same, the product yield is 80%, the purity is 96%; the reaction rate is significantly reduced, and the impurity content in the product is significantly increased.

[0045] Example 20 The difference between this embodiment and Example 1 is that the solvent-free etherification temperature is 80 °C, while the rest of the operation is the same, and the product yield is 69%.

[0046] Example 21 The difference between this embodiment and Example 1 is that the solventless etherification temperature was 105 °C, while the rest of the operation was the same. The product yield was 79.3% and the product purity was 94.7%.

[0047] Examples 1, 20, and 21 show that at lower temperatures (80 °C), the reaction rate is slow, and even with extended reaction time, the yield is still less than 70%, and a large amount of incompletely converted intermediate B is detected in the product. As the temperature increases to 90-100 °C, the reaction rate accelerates significantly, the yield increases to about 80%, and the product purity reaches 99%. When the temperature further increases to above 105 °C, although the reaction rate continues to increase, the frequency of side reactions also increases, leading to an increase in the impurity content in the product and a drop in purity below 95%. Based on the experimental results, the suitable reaction temperature range is determined to be 90-100 °C. Within this range, a high reaction rate can be guaranteed while effectively controlling the occurrence of side reactions, thereby achieving the dual goals of high yield and high purity.

[0048] Example 22 The difference between this embodiment and Example 1 is that the solvent-free etherification reaction time is 6 hours, while the rest of the operation is the same, and the product yield is 65%.

[0049] Example 23 The difference between this embodiment and Example 1 is that the solventless etherification reaction time is 9 hours, while the rest of the operation is the same. The product yield is 78% and the product purity is 94%.

[0050] Example 24 The difference between this embodiment and Example 1 is that the solventless etherification reaction time was 14 h, while the rest of the operation was the same. The product yield was 79% and the product purity was 94%.

[0051] As can be seen from Examples 1 and 22-24, in the initial stage of the reaction (6 h), the target yield is low, only about 65%, because the reaction has not yet reached equilibrium, and the impurity content and purity of the product are high. As the reaction time is extended to 9 h, the yield increases significantly to 78%, but the purity remains at about 94%. When the reaction time is further extended to 11 h, the yield reaches a peak of about 82%, and the purity increases to over 99%, indicating that the reaction is close to complete at this point. Continuing to extend the reaction time to 14 h does not significantly increase the yield; instead, the purity decreases due to the aggravation of side reactions. Therefore, the optimal reaction time is determined to be 11 h, which can minimize the impact of side reactions on product purity while ensuring a high yield.

[0052] Example 25 The difference between this embodiment and Example 1 is that the montmorillonite-supported aluminum trichloride is replaced with Amberlyst 15 cation exchange resin. The rest of the operation is the same, and the product yield is 80%.

[0053] Example 26 The difference between this embodiment and Example 1 is that the montmorillonite-supported aluminum trichloride is replaced with sulfonated graphene, while the rest of the operation is the same, and the product yield is 81%.

[0054] Example 27 The difference between this embodiment and Example 1 is that tetrabutylammonium bromide is replaced with trioctylmethylammonium chloride, and the molar ratio of trioctylmethylammonium chloride to potassium carbonate is 1:18. The rest of the operation is the same, and the product yield is 80%.

[0055] Example 28 The difference between this embodiment and Example 1 is that tetrabutylammonium bromide is replaced with Aliquat 336, and the molar ratio of Aliquat 336 to potassium carbonate is 1:22. The rest of the operation is the same, and the product yield is 81%.

[0056] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this application, "multiple" means two or more, unless otherwise explicitly specified.

[0057] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A method for synthesizing the light stabilizer TINUVIN-1600 using solvent-free condensation technology, characterized in that, Specifically, the following steps are included: (a) Friedel-Crafts reaction: Biphenyl and cyanuric chloride are added to a reaction vessel in a gas atmosphere and melted. Then, a solid acid catalyst is added to carry out the Friedel-Crafts reaction to generate intermediate A. (ii) Solvent-free condensation: The intermediate A is mixed and melted with resorcinol, trifluoromethanesulfonic acid co-catalyst is added, and the condensation reaction is carried out by staged heating, and the intermediate B is generated by post-processing. (III) Solvent-free etherification: The intermediate B and the basic compound catalyst are added to the reaction vessel, and haloisooctane is added in a gas atmosphere to carry out the etherification reaction. After post-treatment, TINUVIN-1600 is obtained.

2. The method for synthesizing the light stabilizer TINUVIN-1600 using a solvent-free condensation technique according to claim 1, characterized in that, The molar ratio of biphenyl to cyanuric chloride is 1:0.4-0.6; the molar ratio of intermediate A to resorcinol is 1:1.0-1.5; and the molar ratio of intermediate B to isooctane is 1:2.2-2.

5.

3. The method for synthesizing the light stabilizer TINUVIN-1600 using a solvent-free condensation technique according to claim 1, characterized in that, The solid acid catalyst in step (i) is one of montmorillonite-supported aluminum trichloride, Amberlyst 15 cation exchange resin, or sulfonated graphene; the molar ratio of biphenyl to solid acid catalyst is 1:0.3-0.

6.

4. The method for synthesizing the light stabilizer TINUVIN-1600 using a solvent-free condensation technique according to claim 1, characterized in that, In step (1), the gas atmosphere is nitrogen, the melting temperature is 80-85 ℃, the Friedel-Crafts reaction temperature is 95-100 ℃, and the time is 6-8 h.

5. The method for synthesizing the light stabilizer TINUVIN-1600 using a solvent-free condensation technique according to claim 1, characterized in that, The melting temperature in step (ii) is 110 °C, the dropping temperature of the trifluoromethanesulfonic acid co-catalyst is 115-120 °C, the dropping time is 30 min, and the molar ratio of intermediate A to the trifluoromethanesulfonic acid co-catalyst is 1:0.05-0.

08.

6. The method for synthesizing the light stabilizer TINUVIN-1600 using a solvent-free condensation technique according to claim 1, characterized in that, The segmented heating in step (II) is as follows: react at 120 ℃ for 3 h, and react at 125-130 ℃ for 4-5 h.

7. The method for synthesizing the light stabilizer TINUVIN-1600 using a solvent-free condensation technique according to claim 1, characterized in that, The post-treatment described in step (ii) is as follows: add one times the amount of deionized water to the system for crystallization, and wash the crystallized solid with hot water at 70 ℃.

8. The method for synthesizing the light stabilizer TINUVIN-1600 using a solvent-free condensation technique according to claim 1, characterized in that, The alkaline composite catalyst in step (iii) is a mixture of potassium carbonate and a quaternary ammonium salt, wherein the quaternary ammonium salt is one of tetrabutylammonium bromide, trioctylmethylammonium chloride, or Aliquat 336; the molar ratio of the quaternary ammonium salt to potassium carbonate is 1:18-22; and the molar ratio of intermediate B to the alkaline composite catalyst is 1:2.3-2.

5.

9. The method for synthesizing the light stabilizer TINUVIN-1600 using a solvent-free condensation technique according to claim 1, characterized in that, Step (3) The temperature at which haloisooctane is added is 90 °C, the temperature of the etherification reaction is 90-100 °C, and the time is 10-12 h; the haloisooctane is bromoisooctane or chloroisooctane.

10. The method for synthesizing the light stabilizer TINUVIN-1600 using a solvent-free condensation technique according to claim 1, characterized in that, The post-treatment described in step (iii) is as follows: After the reaction is completed, the temperature is lowered to 50 °C, 1.5 times the volume of saturated brine is added and stirred for 30 min. After standing and separating into layers, the upper organic phase is taken out, excess bromoisooctane is removed by vacuum distillation, and then recrystallized with n-heptane. After filtration and drying, the TINUVIN-1600 product is obtained.